KARAKTERISASI EKSTRAK ETANOL BUNGA TANAMAN TEMBELEKAN (Lantana camara L.) - Asmi Randa Sosang; Mappiratu Mappiratu; Ruslan Ruslan (KOVALEN: Jurnal Riset Kimia, 2016)
Research on the characterization of the ethanol extract of the flowers of tembelekan (Lantana camara L) has done. This study aims are to determine: (1) the functional group and the absorption spectrum of ethanol extract of flowers tembelekan, (2) the type of eluent used for separating the colored substance ethanol extracts of flowers tembelekan by TLC, (3) absorption spectrum and FTIR extracts and results of separation preparative TLC. Achievement of the objectives is done through the ethanol extract of flowers tembelekan by maceration, followed by taking the spectrum of UV-Vis and FTIR as well as analysis by TLC. The results showed extract ethanol absorbs light at a wavelength of 330 nm which gives an indication that there is a possibility flavonoids, flavonols and flavones. Good eluent use in the separation of components using preparative TLC were eluent a mixture of butanol / acetic acid / water = 4: 1: 5 (v / v / v), which gives an indication of at least one type of compounds in the extract, such as yellow, which has a functional group the free hydroxy group, bonded hydrogen bonding and group C=O.Keywords : flower extract tembelekan , TLC , FTIR spectra